2019
DOI: 10.1103/physreve.99.012322
|View full text |Cite
|
Sign up to set email alerts
|

Link persistence and conditional distances in multiplex networks

Abstract: Recent progress towards unraveling the hidden geometric organization of real multiplexes revealed significant correlations across the hyperbolic node coordinates in different network layers, which facilitated applications like trans-layer link prediction and mutual navigation. But are geometric correlations alone sufficient to explain the topological relation between the layers of real systems? Here we provide the negative answer to this question. We show that connections in real systems tend to persist from o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…We also note that memory in the dynamic-S 1 is induced only via the nodes' latent variables (κ, θ). Extensions to the model with link persistence, where connections/disconnections can also be copied from the previous to the next snapshot [49,50], would allow additional control over the rate of dynamics, i.e., on how fast the topology changes from snapshot to snapshot. The dynamic-S 1 or extensions of it may apply to other types of timevarying networks, such as the ones considered in [51,52], and constitute the basis of maximum likelihood estimation methods that infer the node coordinates and their evolution in the latent spaces of real systems [53].…”
Section: Discussionmentioning
confidence: 99%
“…We also note that memory in the dynamic-S 1 is induced only via the nodes' latent variables (κ, θ). Extensions to the model with link persistence, where connections/disconnections can also be copied from the previous to the next snapshot [49,50], would allow additional control over the rate of dynamics, i.e., on how fast the topology changes from snapshot to snapshot. The dynamic-S 1 or extensions of it may apply to other types of timevarying networks, such as the ones considered in [51,52], and constitute the basis of maximum likelihood estimation methods that infer the node coordinates and their evolution in the latent spaces of real systems [53].…”
Section: Discussionmentioning
confidence: 99%
“…Trans-layer link prediction is about finding missing links in one layer using a similarity measure on another layer, and its effectiveness has been evaluated in contrast to binary link predictor which is based on edge overlap. Also, it is shown that geometric correlations are not enough to explain the high edge overlap in real multiplex networks and a link persistence factor can both improve the reproduction of edge overlap and improve performance of trans-layer link prediction [29].…”
Section: Related Workmentioning
confidence: 99%
“…That is, every user must be labelled with the same pseudonym throughout the sequence of snapshots where it appears. Consistent annotation is of paramount importance for a number of analysis tasks such as community evolution analysis [6], link prediction [15], link persistence analysis [25], among others, that require to track users along the sequence of releases. The data owner anonymises every snapshot exactly once.…”
Section: Overviewmentioning
confidence: 99%
“…As we discussed in Sect. 3.2, the data owner must assign the same pseudonym to each user throughout the subsequence of snapshots where it appears, to allow for analysis tasks such as community evolution analysis [6], link prediction [15], link persistence analysis [25], etc. Since the data owner cannot distinguish between legitimate users (including victims) and sybil accounts, she will assign time-persistent pseudonyms to all of them.…”
Section: Temporal Consistency Constraintsmentioning
confidence: 99%
See 1 more Smart Citation